Designing participation: reconfiguring the roles of civil servants in design-driven governance - Petra Sintorn; Sofia Lundmark (International Journal of Public Sector Management, 2026)
Purpose In their ambition to create citizen participation, public organisations need to change, becoming more open, citizen-centric, and collaborative. This involves designing services and policies in dialogue with citizens, not merely for them. Design methods are increasingly entering the public domain. This study aims to investigate how civil servants perceive and enact design thinking in relation to citizen participation. Design/methodology/approach We conducted a field intervention in which design experts, municipal practitioners, and researchers co-developed and implemented an introduction to design thinking. Findings We identify tensions and role conflicts that constrain the use of design methods. Based on how the civil servants perceive their roles and how they anticipate them in the future, we conceptualise them as role reconfigurations. The four role reconfigurations are: from effective to explorative, from process-coherent to fail-fast, from administrator to innovator, and from expert to facilitator. Originality/value These findings highlight conditions for integrating design-driven approaches in public governance. These role reconfigurations show how civil servants can adopt new positions in a changing governance landscape shaped by design practice and citizen involvement. They also underscore that the sustainable implementation of design thinking requires method training but also institutional support for new mindsets, responsibilities, and relational work.